ANALISIS JARINGAN SOSIAL PENGGUNA TWITTER DALAM SKEMA PENYEDIAAN LAPTOP BAGI TOKO KOMPUTER - Rama Tri Budi Ardianto; Yessica Nataliani (Fakultas Teknologi Informasi, Universitas Kristen Satya Wacana, 2023)
Twitter is a social media that provides information for its users. Interactions on Twitter may increase the amount of data from its users. Business development cannot be separated from product competition between business actors. One way for companies to win the competition is to know the purchasing power of customers. A product's selling power can be known one way or another through user interaction on Twitter. User-generated content (UGC) results from data on Twitter. UGC data can be used to determine the product supply scheme taken by laptop products in this study. The method used to analyze the interaction is Social Network Analysis (SNA) by comparing the properties of the network. Social network modeling on UGC data was carried out on three laptops: Lenovo v14, Asus ZenBook S, and Acer Swift 3. From the graph visualization, it was found that Acer excels in two properties, namely